5FU/Oxaliplatin-Induced Jagged1 Cleavage Counteracts Apoptosis Induction in Colorectal Cancer: A Novel Mechanism of Intrinsic Drug Resistance - Pelullo, Maria; Zema, Sabrina; De Carolis, Mariangela; Cialfi, Samantha; Giuli, Maria Valeria; Palermo, Rocco; Capalbo, Carlo; Giannini, Giuseppe; Screpanti, Isabella; Checquolo, Saula; Bellavia, Diana (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is characterized by early metastasis, resistance to anti-cancer therapy and high mortality rate. Despite considerable progress in development of new treatment options that improved survival benefits in patients with early stage or advanced CRC, many patients relapse due to activation of intrinsic or acquired chemoresistance mechanisms. Recently, we reported novel findings about Jagged1 role in CRC tumors with Kras signatures. We showed that Jagged1 is a novel proteolytic target of Kras signaling, which induces Jagged1 processing/activation resulting in Jag1-ICD release, which favours tumor development in vivo, through a non-canonical mechanism. Herein, we demonstrate that OXP and 5FU cause a strong accumulation of Jag1-ICD oncogene, through ERK1/2 activation, unveiling a surviving subpopulation with an enforced Jag1-ICD expression, presenting the ability to counteract OXP/5FU-induced apoptosis. Remarkably, we also clarify the clinical ineffectiveness of GSIs in mCRC patients. Indeed, we show that GSI compounds trigger Jag1-ICD release that promotes cellular growth and EMT processes, functioning as tumor-promoting agents in CRC cells over-expressing Jagged1. We finally demonstrate that Jagged1 silencing in OXP- or 5FU-resistant subpopulations is enough to restore the sensitivity to chemotherapy, confirming that drug sensitivity/resistance is Jag1-ICD-dependent, suggesting Jagged1 as a molecular predictive marker for the outcome of chemotherapy.